Politics and Islamic Laws in Indonesia (Case Study of Muslim Prayer Procedures During the Covid-19 Pandemic) - Delmus Puneri Salim (Mazahib, 2022)
Scholars have analyzed the increasing implementation of Islamic laws in Indonesia after the 1998 reform. They have shown that traditional Islamic laws practiced in the past are being implemented again today, such as caning in Aceh, hijab for women in West Sumatra, and the obligation of Qur’anic literacy in South Sulawesi. Few scholars show otherwise about rational and accommodating laws in contemporary Islamic laws. By analyzing fatwas, circulars, and instructions issued by three prominent Islamic institutions in Indonesia regarding the procedures for praying during the Covid-19 pandemic, this article shows, as Jeremy Menchik (2014) pointed out, that Islamic laws are changeable and can be influenced by science and government and non-government institutions. The Muslim prayer procedures during the Covid-19 pandemic show that while Islamic authorities are still crucial in managing Muslim societies, their interpretation of Islamic laws is subject to change from time to time. The results of this study imply that Islamic institutions and government and non-government institutions can work together in managing contemporary Muslim societies utilizing progressive interpretations of sharia. Keywords: Politics, Islamic laws, Covid-19, Islam, Indonesia